Relationship between Parental Attention and Study Habits with Social Studies Learning Outcomes - Fauzi, Achmad (Universitas Negeri Semarang, 2021)
The objective of this research was to examine the correlation beetween parental attention and study habits with socialstudies learning outcomes of 5th grade Gugus Handaka Elementary School Pringsurat District, Temanggung Regency.This study was a quantitative research. The researcher used correlation design research. The technique of taking samplewas by using probability sampling, resulting in 102 participants. Data collection techniques were questionnaires,interviews, and documentation. These data were analyzed by applying descriptive statistics analyzed and product momentanalysis. The result of this research showed that (1) there was a positive and significant correlation between parentalattention and social studies learning outcomes, with a total correlation coefficient value of 0.731 and a contribution of53.43%; (2) there was a positive and significant correlation between study habits and social studies learning outcomeswith a total correlation coefficient value of 0.820 and a contribution of 67.24%; (3) there was a positive and significantcorrelation between parental attention and study habits toward social studies learning outcomes, its total correlationcoefficient value of 0.841 and a contribution of 70.72%.Keywords: Parental Attention, Study Habits, Social Studies Learning Outcomes